THE INFLUENCE OF EMPLOYEE PERFORMANCE ON SERVICE QUALITY IN BUNTULIA DISTRICT OFFICE - Pakaya, Abdul Malik; Abdussamad, Juriko; Tui, Fenti Prihatini (Universitas Negeri Gorontalo, 2024)
This study aims to determine the effect of employee performance on service quality at the Buntulia District Office. The research method used in this study is the quantitative method, where the sample in this study amounted to 30 employees and 30 people from the Buntulia District community using a research approach and research design. Data collection techniques were carried out by distributing questionnaires to research respondents. The data analysis technique used is simple regression analysis. The results of the regression analysis test showed that there was a significant effect on employee performance on service quality at the Buntulia District Office. The first hypothesis (H1) can be proven or accepted. The R Square value is 0.342 in other words 34.2% of the independent variables namely (X) Employee Performance contributes to the variable (Y) Quality of Service, while the remaining 65.8% is in the form of contributions from other variables not examined in this study.